2021
DOI: 10.3389/fnhum.2021.702520
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Sensory Predictions: A Review of Predictive Mechanisms in the Brain and Their Link to Conscious Processing

Abstract: The human brain has the astonishing capacity of integrating streams of sensory information from the environment and forming predictions about future events in an automatic way. Despite being initially developed for visual processing, the bulk of predictive coding research has subsequently focused on auditory processing, with the famous mismatch negativity signal as possibly the most studied signature of a surprise or prediction error (PE) signal. Auditory PEs are present during various consciousness states. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 290 publications
(451 reference statements)
0
10
0
1
Order By: Relevance
“…Some deep meditative states are associated with the global dissolution of the embodied self [Millière et al, 2018] and can thus serve as unique models for a neurophenomenological investigation of self-dissolution (disengagement of self-models). Recent conceptual mechanistic frameworks of meditation practice have suggested that predictive processing accounts [Lutz et al, 2019;Laukkonen & Slagter, 2021;Tivadar et al, 2021], as well as measures of complexity [Schartner et al, 2017a;Escrichs et al, 2019;Luppi et al, 2021], may be fruitful for bridging experiential and neural dynamics.…”
Section: Neurophenomenology: Probing the Structure Of Experiencementioning
confidence: 99%
“…Some deep meditative states are associated with the global dissolution of the embodied self [Millière et al, 2018] and can thus serve as unique models for a neurophenomenological investigation of self-dissolution (disengagement of self-models). Recent conceptual mechanistic frameworks of meditation practice have suggested that predictive processing accounts [Lutz et al, 2019;Laukkonen & Slagter, 2021;Tivadar et al, 2021], as well as measures of complexity [Schartner et al, 2017a;Escrichs et al, 2019;Luppi et al, 2021], may be fruitful for bridging experiential and neural dynamics.…”
Section: Neurophenomenology: Probing the Structure Of Experiencementioning
confidence: 99%
“…The MMN is a negative wave generally peaking over fronto-central scalp electrodes between 100 and 250 milliseconds, with variations depending on the experimental design including the dimension of the deviant feature [1]. Discovered more than 40 years ago [4], it was investigated in research fields as broad as neurolinguistics [5], attention [6], altered states of consciousness [7, 8], aging [9], psychiatry [10, 11], emotions [12], psychedelics [13] or meditation [14]. However, despite its use in clinical research or as an experimental measure for many cognitive functions [15], its generative mechanisms are still widely debated.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in response to LGP, a local mismatch response was registered across NREM1, NREM2, and REM but with an incomplete structure, and neither the classical MMN/P3a complex nor P300 was detected [ 32 ]. During SWS, most researchers failed to find any response, even on local irregularities [ 36 , 37 ]. However, some questions are still not answered: At which point in the continuum of the transition from sleep to wakefulness emerges the processing of global irregularities?…”
Section: Introductionmentioning
confidence: 99%